Efforts To Prevent Forest And Land Fires Through Community Empowerment Patterns In The Manggala Agni Daops Activities Sumatra Ix/Jambi City - Mariani Dewi sartika Panggabean; Marwoto Marwoto; Rince Muryunika (Universitas Muhammadiyah Palembang, 2025)
Forest and land fires (karhutla) are ecological problems that continue to recur in Jambi Province, especially in peatland areas that are highly vulnerable to fire hotspots. Pulau Mentaro Village and Puding Village in Kumpeh District are areas with a high level of vulnerability due to peat characteristics and pressures from human activities. This study aims to analyze the implementation of the forest and land fire prevention program through community empowerment patterns by Manggala Agni Daops Sumatra IX/Jambi City, as well as to identify internal and external factors affecting the program using SWOT analysis. The study was conducted from March to May 2025 using a descriptive qualitative and quantitative approach, involving 32 respondents through in-depth interviews, observation, and documentation studies. The results show that the forms of empowerment that have been implemented include training for Fire Care Communities (MPA), counseling, socialization, early prevention, and seasonal patrols. The SWOT analysis shows a strength score of 2.8, a weakness score of 2.9, an opportunity score of 3, and a threat score of 2.9, placing the program in Quadrant III (WO Strategy). This position indicates the need for a